Quality Evaluation of Whole Wheat Sourdough Fermented at Different Temperatures and Diversity Analysis and Breeding Selection of Lactic Acid Bacteria - Bo WANG; Weiqing ZHANG; Han GAO; Chao WANG; Yuchun LIU; Chao GUO (Shipin gongye ke-ji)
To investigate the impact of fermentation temperature on the quality and biodiversity of lactic acid bacteria (LAB) in whole wheat sourdough, full-length high-throughput sequencing technology was applied to systematically analyze the community structure and succession patterns of bacterial communities in sourdough samples fermented at different temperatures during the maturation process. Sourdough quality was assessed by physicochemical analysis, and dominant bacterial strains were isolated using traditional cultivation methods and then screened for unique characteristics. The results indicated that high temperature fermentation could impart better quality characteristics to whole wheat sourdough. There was a significant effect of fermentation temperature on sourdough quality characteristics. The pH of the matured sourdough decreased from 4.18 to 3.87 and the total titratable acidity (TTA) increased from 15.0 mL to 24.0 mL with increasing fermentation temperature. The total antioxidant activity, flavonoids and amino acid content of ripened sourdough increased significantly when the fermentation temperature was not lower than 30 ℃ (P<0.05). There were significant differences in the dominant lactic acid bacteria between ripened whole wheat sourdough fermented at different temperatures. The Latilactobacillus curvatus predominated at 20 ℃ and 25 ℃, and both Latilactobacillus curvatus and Pediococcus acidilactici were prevalent at 30 ℃. The Limosilactobacillus pontis became the dominant strain when the fermentation temperature was increased to 37 ℃. Enzyme activity screening revealed that LAB 31, identified as Latilactobacillus curvatus, had the highest cellulase activity of 77.92±2.26 U/L and LAB 22, identified as Pediococcus acidilactici, had the highest amylase activity of 42.19±4.12 U/L. This study is expected to provide a theoretical basis and bacterial resources for the development of starter cultures for whole wheat fermentation foods.